Improving succinic acid production by Actinobacillus succinogenes from raw industrial carob pods. (October 2016) - Carvalho, Margarida; Roca, Christophe; Reis, Maria A.M.
Highlights: Water extracts containing 92 g/L sugars can be obtained from raw carob pods. A volumetric productivity of 1.67 g SA/L.h was obtained during batch cultivation. By-products formation was reduced using fed-batch mode, yielding 0.94 g SA/g sugars. Carob pods are an excellent substrate for A. succinogenes and succinic acid production. Abstract: Carob pods are an inexpensive by-product of locust bean gum industry that can be used as renewable feedstock for bio-based succinic acid. Here, for the first time, unprocessed raw carob pods were used to extract a highly enriched sugar solution, afterwards used as substrate to produce succinic acid using Actinobacillus succinogenes . Batch fermentations containing 30 g/L sugars resulted in a production rate of 1.67 g SA/L.h and a yield of 0.39 g SA/g sugars. Taking advantage of A. succinogenes ' metabolism, uncoupling cell growth from succinic acid production, a fed-batch mode was implemented to increase succinic acid yield and reduce by-products formation. This strategy resulted in a succinic acid yield of 0.94 g SA/g sugars, the highest yield reported in the literature for fed-batch and continuous experiments, while maintaining by-products at residual values. Results demonstrate that raw carob pods are a highly efficient feedstock for bio-based succinic acid production.